Spontaneous calcium signaling of cartilage cells: from spatiotemporal features to biophysical modeling. Issue 4 (2nd January 2019) - Zhou, Yilu; Lv, Mengxi; Li, Tong; Zhang, Tiange; Duncan, Randall; Wang, Liyun; Lucas Lu, X.
ABSTRACT: Intracellular calcium ([Ca 2+ ]i ) oscillation is a fundamental signaling response of cartilage cells under mechanical loading or osmotic stress. Chondrocytes are usually considered as nonexcitable cells with no spontaneous [Ca 2+ ]i signaling. This study proved that chondrocytes can exhibit robust spontaneous [Ca 2+ ]i signaling without explicit external stimuli. The intensity of [Ca 2+ ]i peaks from individual chondrocytes maintain a consistent spatiotemporal pattern, acting as a unique "fingerprint" for each cell. Statistical analysis revealed lognormal distributions of the temporal parameters of [Ca 2+ ]i peaks, as well as strong linear correlations between their means and sds . Based on these statistical findings, we hypothesized that the spontaneous [Ca 2+ ]i peaks may result from an autocatalytic process and that [Ca 2+ ]i oscillation is controlled by a threshold‐regulating mechanism. To test these 2 mechanisms, we established a multistage biophysical model by assuming the spontaneous [Ca 2+ ]i signaling of chondrocytes as a combination of deterministic and stochastic processes. The theoretical model successfully explained the lognormal distribution of the temporal parameters and the fingerprint feature of [Ca 2+ ]i peaks. In addition, by using antagonists for 10 pathways, we revealed that the initiation of spontaneous [Ca 2+ ]i peaks in chondrocytes requires the presence of extracellular Ca 2+, and that the PLC‐inositol 1, 4, 5‐trisphosphate pathway, which controls the release of calcium from the endoplasmic reticulum, can affect the initiation of spontaneous [Ca 2+ ]i peaks in chondrocytes. The purinoceptors and transient receptor potential vanilloid 4 channels on the plasma membrane also play key roles in the spontaneous [Ca 2+ ]i signaling of chondrocytes. In contrast, blocking the T‐type or L‐type voltage‐gated calcium channel promoted the spontaneous calcium signaling. This study represents a systematic effort to understand the features and initiation mechanisms of spontaneous [Ca 2+ ]i signaling in chondrocytes, which are critical for chondrocyte mechanobiology.—Zhou, Y., Lv, M., Li, T., Zhang, T., Duncan, R., Wang, L., Lu, X. L. Spontaneous calcium signaling of cartilage cells: from spatiotemporal features to biophysical modeling. FASEB J. 33, 4675–4687 (2019). www.fasebj.org